2019
DOI: 10.1093/jhps/hnz004
|View full text |Cite
|
Sign up to set email alerts
|

Comparable patient-reported outcomes in females with or without joint hypermobility after hip arthroscopy and capsular plication for femoroacetabular impingement syndrome

Abstract: Hip arthroscopy is widely utilized to treat femoroacetabular impingement syndrome (FAIS). In order to evaluate the postoperative clinical and functional outcomes at 2-year follow up in patients with and without benign joint hypermobility syndrome following hip arthroscopy with capsular plication for FAIS, consecutive female patients with generalized ligamentous laxity undergoing primary hip arthroscopy with complete T-capsulotomy closure via plication for FAIS were prospectively identified. Patients were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…Regarding latest follow-up specific to hip preservation–designed PRO results, no differences were found. The authors of the previous study 75 stated that appropriate capsular management is essential to achieve good results in GLL populations, and we agree with this concept in addition to the combination of labral function/seal restoration. 2,24,59 In almost 94% of the patients, the capsule was plicated.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Regarding latest follow-up specific to hip preservation–designed PRO results, no differences were found. The authors of the previous study 75 stated that appropriate capsular management is essential to achieve good results in GLL populations, and we agree with this concept in addition to the combination of labral function/seal restoration. 2,24,59 In almost 94% of the patients, the capsule was plicated.…”
Section: Discussionsupporting
confidence: 83%
“…With longer follow-up, Stone et al 75 recently published their results regarding patients with GLL (Beighton score ≥4) who underwent hip arthroscopy. The authors reported similar improvement in outcomes at average 2-year follow-up to a matched control group based on Δ value for mHHS ( P = .913), HOS-SSS ( P = .944), HOS–Activities of Daily Living ( P = .618), and VAS ( P = .512).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsular management after hip arthroscopy varies among surgeons, ranging from T-capsulotomy without closure (TC) to partial closure of the T-capsulotomy and interportal capsulotomy with or without closure. 2,10,12,13,15,16,20,28,29. No consensus has been defined regarding the best approach to capsular management.…”
mentioning
confidence: 99%
“…Previous authors have reported good outcomes in female patients with hypermobility by use of an arthroscopic approach with capsular plication. 10 However, this finding cannot be generalized to the dancer's hip. In addition, it would have been interesting to report the reason that 16% of dancers did not return to the previous level of activity.…”
mentioning
confidence: 95%